ENTREPRENEURSHIP INTENTIONS OF SFAX UNIVERSITY STUDENTS - Morched, Salim; Haj Brahim, Abdallah; Jarboui, Anis (Journal of Business And Entrepreneurship, 2022)
In Tunisia, the job that thousands of university graduates aim to do is their first choice, not to initiate their own business. This research aims to examine the entrepreneurial mentality of Sfax University students and their objectives of starting a new business by studying the disadvantages preventing them from becoming independent. First, collecting key data through self-prepared questionnaires is done for the evaluation of the explanatory factor’s role, such as attitudes, senses of control, social norms, and students’ perceptions of entrepreneurship, and how each dimension affects entrepreneurs’ intentions. Then, the use of a multiple regression model based on Ajzen’s (1991) Theory of Planned Behavior (TPB) is effective to analyze the data. After receiving entrepreneurship training at the University of Sfax, this theoretical framework was verified by 320 students from different disciplines. The results show that personal attitudes and perceived behavioral control are the explanation of entrepreneurial intentions.